Long-term treatment outcomes with zygomatic implants: a systematic review and meta-analysis - Matthew Brennand Roper; Arjan Vissink; Tom Dudding; Alex Pollard; Barzi Gareb; Chantal Malevez; Thomas Balshi; Lawrence Brecht; Vinay Kumar; Yiqun Wu; Ronald Jung (SpringerOpen, 2023)
Abstract Purpose The purpose of this study was to perform a systematic review with meta-analysis on the long-term survival rates of zygomatic implants (ZI). ZI success, prostheses survival and success, sinus pathology and patient reported outcomes were also investigated. Methods Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) guidelines were followed. Embase and OvidMedline databases were searched alongside the grey literature. The systematic review was recorded in PROSPERO (CRD42022358024). Studies reporting titanium/titanium alloy ZI survival data, ZI-supported prosthesis data, ZIs directly compared to any other implant therapy including grafted sites, a minimum follow-up time of 3 years and a minimum number of 10 patients were included. All study designs were considered if they met the inclusion criteria. Studies not involving ZIs, ZIs not made from titanium/titanium alloy, a follow-up time of < 3 years or < 10 patients, animal studies and in vitro studies were excluded. Long-term follow-up has not been defined in the literature. A minimum of 3 years follow-up was considered acceptable to capture survival after initial healing, alongside in-function prosthesis data via delayed or immediate load protocols. ZI success, was predominantly defined as ZI survival without biological or neurological complications. Meta-analyses were performed for ZI survival, ZI failure incidence, ZI success, loading protocol, prosthesis survival, and prevalence of sinusitis using random effects models. Descriptive analysis was used for ZI success, prosthesis success and patient reported outcome measures. Results Five hundred and seventy-four titles were identified, of which 18 met the inclusion criteria. Eligible studies included 1349 ZIs in 623 patients. Mean follow-up period was 75.4 months (range 36-141.6). The mean survival of ZIs was 96.2% [95% CI: 93.8; 97.7] at 6 years. Mean survival for delayed loading was 95% [95% CI: 91.7; 97.1] and 98.1% [95% CI: 96.2; 99.0] for immediate loading (p = 0.03). Annual incidence rate of ZI failure was 0.7% [95% CI 0.4; 1.0]. Mean ZI success was 95.7% [95% CI 87.8; 98.6]. Mean prosthesis survival was 94% [95% CI 88.6; 96.9]. Sinusitis prevalence was 14.2% [95% CI 8.8; 22.0] at 5 years. Patients' reported increased satisfaction with ZIs. Conclusions ZIs have long-term survival comparable to conventional implants. Immediate loading showed a statistically significant increase in survival over delayed loading. Prosthesis survival was similar to that of prostheses supported by conventional implants, with similar complications. Sinusitis was the most frequently encountered biological complication. Patients reported improved outcome measures with ZI use. Graphical Abstract